Ten-year (2009–2019) epidemiological study of head and neck, salivary glands and upper aerodigestive tract cancers, and overall survival outcomes in the Northern Territory of Australia - Hemi Patel; Nayellin Reyes-Chicuellar; Kate Thimbleby; Bhavya Balasubramanya; Suresh Mahendran (BMJ Public Health)
Background Head and neck, salivary glands and aerodigestive tract cancers (HNACs) rank sixth in cancer incidence in Australia, posing significant public health and economic challenges. However, data on HNACs in the Northern Territory (NT) are lacking, crucial for healthcare planning.Objective This study aims to analyse HNACs epidemiology, risk factors and survival outcomes in the NT, focusing on Indigenous and non-Indigenous Australians.Methods We conducted a retrospective analysis (2009–2019) of HNACs cases from the NT Cancer Registry. Ethically approved, the study assessed incidence, mortality, risk factors and survival across ethnic populations.Results Of 612 potential cases, 524 were analysed, with 35.5% identifying as Aboriginal or Torres Strait Islanders. Predominantly affecting males (median age: 62 years), HNACs showed an age-standardised incidence of 21.9 per 100 000, with stable trends. The 5-year survival rate was 39.6%, notably lower in Indigenous Australians (25%) and remote areas (18%) vs the national average (68%). Oropharyngeal malignancies were common (36% survival). High-risk behaviours such as alcohol use (73%) and smoking (91%) prevailed. Most patients (73%) presented with advanced disease (stages III–IV), with one-third offered palliative care at diagnosis. P16-negative tumours predominated, with increasing P16-positive cases in non-Indigenous patients.Conclusion HNACs survival rates in the NT are significantly lower than the national average, especially among Indigenous Australians and remote residents. Targeted interventions are needed to improve service planning and delivery, considering identified risk factors and cultural sensitivities, and promoting Indigenous participation.